2006
DOI: 10.1097/01.qco.0000199020.58075.1a
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted diseases in incarcerated adolescents

Abstract: The high prevalence of chlamydia in incarcerated adolescents and gonorrhea in incarcerated adolescent women suggests that screening of these populations should be a priority. The reasons for the higher prevalence of chlamydia and gonorrhea in young adults aged 18-19 years incarcerated in selected adult corrections facilities compared with those incarcerated in juvenile facilities should be investigated. Hepatitis B virus vaccination in juvenile correction facilities is recommended to prevent and control the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…High T. vaginalis prevalence (32%) has been observed among women incarcerated in San Francisco county jail (10). Similar findings relating to C. trachomatis and N. gonorrhoeae infections were reported for black adolescents 18 to 19 years old who were incarcerated in adult correction facilities (19). Although women attending STD clinics are expected to have high T. vaginalis, C. trachomatis, and N. gonorrhoeae rates due to high-risk behavior and/or symptomatic status, providers should be aware of the high T. vaginalis rates in the hospital setting.…”
Section: Discussionsupporting
confidence: 69%
“…High T. vaginalis prevalence (32%) has been observed among women incarcerated in San Francisco county jail (10). Similar findings relating to C. trachomatis and N. gonorrhoeae infections were reported for black adolescents 18 to 19 years old who were incarcerated in adult correction facilities (19). Although women attending STD clinics are expected to have high T. vaginalis, C. trachomatis, and N. gonorrhoeae rates due to high-risk behavior and/or symptomatic status, providers should be aware of the high T. vaginalis rates in the hospital setting.…”
Section: Discussionsupporting
confidence: 69%
“…More recently, the CDC (2006) reported a 6.3% median state STD positive rate for women aged 15 to 24 tested at family clinics, whereas the median percent positive rate for females tested in juvenile correctional facilities was 14.2%. Contributing to public health concerns regarding these alarming STD prevalence rates, a majority of juvenile offenders do not have regular sources of health care, access to HIV and STD testing and education, and/or the resources to obtain such services (Joesoef et al 2006). Hence, large populations of youthful offenders are unlikely to receive STD education and treatment, and in turn, are more likely to be living with these infections.…”
Section: Risky Sexual Practices and Stds Among Juvenile Offendersmentioning
confidence: 99%
“…The determinants underlying the disproportionate burden of disease among African-American youth are complex and likely include the underlying high disease prevalence in the community, poverty, low male:female sex ratio, and high rates of incarceration in this population. (6, 7) Multiple studies have identified the strong link between incarceration and increased STI risk among individuals, (8, 9) and between incarceration and increased sexual risk behaviours, including concurrency and multiple sexual partners. (8, 10, 11) Young African-American women with a male sexual partner recently released from jail have been found to have increased risk of acquiring chlamydia.…”
Section: Introductionmentioning
confidence: 99%